PREVENTION OF ARSHAS WITH REFERENCE TO LIFESTYLE CHANGES: SCOPE IN AYURVEDA - P.V, Dhanya; Bharadwaj, Anjali; Mishra, Baidyanath (International Journal of Ayurveda and Pharma Research, 2015)
Arshas or hemorrhoid is quite a common problem observed both in men and women. It can be a recurrent and painful intrusion in life. Even young people who are in good shape can get Arshas. The incidence of Arshas is increasing day by day due to the influence of western food habits, diet which contains very less amount of soluble fibre, inappropriate diet regimen and Vegadharana (suppression of natural urge to defecate) which causes constipation. Other factors which trigger Arshas are improper toilet habits, sedentary work style or strenuous work, prolonged periods of standing or sitting, prolonged travelling on two wheelers and overweight. Its incidence increases as age advances, and at least 50% of people over the age of 50 years have some degree of hemorrhoidal symptoms. Therefore, simple lifestyle changes can effectively reduce the recurrence of this common and painful condition. There is a wide spread description of etiological factors and pathogenesis of Arshas in Ayurvedic literatures as well as surgical textbooks. The measures of prevention such as implementing various Pathyapathyas with respect to Ahara and Vihara (diet regimen and simple life style changes) have great importance in the present day scenario. By understanding the Nidana and samprapti the various preventive measures can be interpreted rightly and implemented so that it will prevent the disease Arshas. Therefore the need for the understanding of the Pathyapathya of Arshas along with certain life style changes becomes valuable for the common man as well as the physicians in the preventive and the curative aspects of the disease. There by, we can prevent occurrence and recurrence of Arshas.